Co-production of Xylooligosaccharides and Xylose From Poplar Sawdust by Recombinant Endo-1,4-β-Xylanase and β-Xylosidase Mixture Hydrolysis - Li, Qi; Jiang, Yunpeng; Tong, Xinyi; Zhao, Linguo; Pei, Jianjun (Frontiers in Bioengineering and Biotechnology, 2021)
As well known, endo-1,4-β-xylanase and β-xylosidase are the rate-limiting enzymes in the degradation of xylan (the major hemicellulosic component), main functions of which are cleavaging xylan to release xylooligosaccharides (XOS) and xylose that these two compounds have important application value in fuel, food and other industries. This study focuses on enzymatic hydrolysis of poplar sawdust xylan for production of XOS and xylose by a GH11 endo-1,4-β-xylanase MxynB-8 and a GH39 β-xylosidase Xln-DT. MxynB-8 showed excellent ability to hydrolyze hemicellulose of broadleaf plants such as poplar. Under optimized conditions (50oC, pH 6.0, dosage of 500 U/g, substrate concentration of 2 mg/mL), the final XOS yield was 85.5%, and the content of XOS2-3 reached to 93.9% after 18 h. The enzymatic efficiency by MxynB-8 based on the poplar sawdust xylan in the raw material was 30.5%. Xln-DT showed excellent xylose/glucose/arabinose tolerance, which supplyed it a candidate to apply in degradation of hemicellulose. In addition, the process and enzymatic mode of poplar sawdust xylan with MxynB-8 and Xln-DT were investigated. The results showed that the enzymatic hydrolysis yield of poplar sawdust xylan was improved by adding Xln-DT, and a xylose-rich hydrolysate could be obtained at high purity, with the xylose yield of 89.9%. The enzymatic hydrolysis yield was higher (32.2%) by using MxynB-8 and Xln-DT together. This study provides a deep understanding of double enzyme synergetic enzymolysis of wood polysaccharides to valuable products.